Heart rate turbulence as risk-predictor after myocardial infarction - Zuern, Christine S.; Barthel, Petra; Bauer, Axel (Frontiers in Physiology, 2011)
Heart Rate Turbulence (HRT) is the baroreflex-mediated short-term oscillation of cardiac cycle lengths after spontaneous ventricular premature complexes (VPC). HRT is composed of a brief heart rate acceleration followed by a gradual heart rate deceleration. In high risk patients after myocardial infarction (MI) HRT is blunted or diminished. Since its first description in 1999 HRT emerged as one of the most potent risk factors after MI. Predictive power of HRT has been studied in more than 10,000 post-infarction patients. This review is intended to provide an overview of HRT as risk predictor after MI.